Brown and Red Seaweeds Serve as Potential Efflux Pump Inhibitors for Drug-Resistant Escherichia coli. (1st January 2019) - Lu, Wen-Jung; Lin, Hsuan-Ju; Hsu, Pang-Hung; Lai, Margaret; Chiu, Jen-Yu; Lin, Hong-Ting Victor
Abstract : Multidrug-resistant pathogens are a significant clinical problem. Efflux pump inhibitors (EPIs) can restore the activities of existing antibiotics by interfering with drug efflux pumps located in bacterial cell membranes. Seaweeds are important sources of biologically active metabolites of natural origin; however, their potential as EPIs remains uninvestigated. Here, functional extracts from the brown seaweeds Laminaria japonica and Sargassum horneri and the red seaweeds Gracilaria sp. and Porphyra dentata were evaluated as potential EPIs against drug-resistant Escherichia coli . All these extracts were found to potentiate the activities of drugs in modulation tests, although not to the same extent. Synergistic effects of the extracts and the drug clarithromycin were observed from the onset of Time-kill assays, with no evidence of bacterial regrowth. Ethidium bromide accumulation studies revealed that the efflux decreased in the presence of each extract, as indicated by the presence of EPIs. Most identified EPIs that have been discovered to date have aromatic structures, and the seaweed extracts were found to contain various terpenes, terpenoids, phenolic compounds, indoles, pyrrole derivatives, alkaloids, and halogenated aromatic compounds. Our study highlights the potential of these compounds of the seaweeds as drug EPIs.